2016
DOI: 10.1080/03019233.2016.1156900
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the decarburisation phenomena during preheating of submerged entry nozzles (SEN) in continuous casting processes

Abstract: PostprintThis is the accepted version of a paper published in Ironmaking & steelmaking. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Svensson, J., Memarpour, A., Brabie, V., Jönsson, P. (2016) Studies of the decarburisation phenomena duringpreheating of submerged entry nozzles (SEN) incontinuous casting processes. Decarburisation of the submerged entry nozzles (SEN) during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…These mechanisms are related to chemistry and thermodynamics of the system. Most studies were made by postmortem analysis of inclusions or clog [13][14][15]30,[39][40][41][42][43] or through thermodynamic calculation of the involved phases (materials) related to clogging. [41,[44][45][46][47] These studies indicated that the clogging event was related to (or affected by) the thermodynamic or chemical properties of the involved materials, but no quantitative correlation between the clogging event and those thermodynamic or chemical properties was established.…”
Section: Model Limitations and Outlookmentioning
confidence: 99%
“…These mechanisms are related to chemistry and thermodynamics of the system. Most studies were made by postmortem analysis of inclusions or clog [13][14][15]30,[39][40][41][42][43] or through thermodynamic calculation of the involved phases (materials) related to clogging. [41,[44][45][46][47] These studies indicated that the clogging event was related to (or affected by) the thermodynamic or chemical properties of the involved materials, but no quantitative correlation between the clogging event and those thermodynamic or chemical properties was established.…”
Section: Model Limitations and Outlookmentioning
confidence: 99%
“…The core concept of high efficiency continuous casting is to produce high quality defect-free steel at high casting speeds. At high casting speeds, slag entrapment in molds seriously deteriorate the quality of steel products, becoming one of the main obstacles affecting the production of high value-added steel products [1].…”
Section: Introductionmentioning
confidence: 99%
“…1 Excellent thermo-mechanical properties, high corrosion resistance against both liquid steel and slag as well as high thermal shock resistance are typical properties that are required for the application of SEN materials. 1 Excellent thermo-mechanical properties, high corrosion resistance against both liquid steel and slag as well as high thermal shock resistance are typical properties that are required for the application of SEN materials.…”
Section: Introductionmentioning
confidence: 99%
“…The submerged entry nozzle (SEN) is one of the most important functional components in the continuous casting of steel, playing critical roles in the production efficiency as well as steel quality. 1 Excellent thermo-mechanical properties, high corrosion resistance against both liquid steel and slag as well as high thermal shock resistance are typical properties that are required for the application of SEN materials. To meet these requirements, Al 2 O 3 -C refractories with graphite content in the range of 8%-25%, were developed in the 1980s and have been increasingly used in the continuous casting since then.…”
Section: Introductionmentioning
confidence: 99%